Recursos através dos ecossistemas: insetos aquáticos emergentes subsidiam comunidade de aranhas ripárias - Recalde Ruiz, Fátima Carolina [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
It is widely known that input of allochthonous subsidies in recipient food webs directly participate in the dynamics of consumers and indirectly on predator-prey interactions. However, this knowledge is based on studies from temperate forests, thus there is still a gap in the knowledge of tropical systems where the abundance and diversity of terrestrial prey is high. In this study, we investigate the effects of emergent aquatic insects on predator-prey dynamics of tropical terrestrial food webs. To test this effect, we excluded allochthonous aquatic insects using greenhouse type exclosures, and allowed emergence of insects through unmanipulated stream reaches using a randomized design. Emergent aquatic insects and terrestrial flying insects were collected through sticky traps. Terrestrial arthropods in shrubs and ground were collected manually in nocturnal and diurnal surveys, and were classified in predators, phytophages, detritivores and omnivores. The abundance of aquatic insects was five times lower in exclosures than control, but there was no effect of treatment on abundance of terrestrial fly insects; abundance of terrestrial insects were three times more abundant that aquatic insects. PERMANOVA revealed that abundance of terrestrial predators, but not their biomass, was affected by exclosure treatment. Univariate analysis show that only 11.5% of predatory taxa (Anyphaenidae, Araneidae and Theridiidae) decreased its abundance in exclosure treatment and only 7.7% of them (Araneidae and Theridiidae) decreased its biomass. Abundance of phytophages, detritivores and omnivores was not affected by treatments, but the biomass of phytophages increased six times in exclosure treatment. Despite the abundance and biomass of only few predators were affected by exclosure, we observed that predators overall derived more than 80% of N and C of aquatic prey. Our results demonstrate that allochthonous subsidies participate on terrestrial food web ...

É amplamente sabido que os subsídios alóctones entram nas teias alimentares receptoras participando diretamente da dinâmica dos consumidores e indiretamente sobre as interações predador-presa. No entanto, este conhecimento se baseia em estudos feitos em florestas temperadas e por conseguinte ainda há lacunas no conhecimento dos sistemas tropicais, onde a abundância e variedade das presas é maior. Neste trabalho, buscamos descrever o efeito dos insetos aquáticos emergentes sobre a dinâmica predador-presa das teias alimentares terrestres presentes em zonas ripárias de uma floresta tropical. Para testar este efeito, utilizamos um desenho experimental de blocos aleatorizados. Deste modo, manipulamos a emergencia de insetos adultos de um riacho, utilizando um tratamento de exclusão com uma cobertura plástica sobre o riacho e um tratamento de controle, onde permitimos a emergência natural dos insetos para a terra. Amostramos os insetos aquáticos emergentes com armadilhas adesivas e os artrópodes terrestres (predadores, fitófagos, onívoros, detritívoros) usando diversos métodos. A abundância de insetos aquáticos emergentes foi cinco vezes menor no tratamento de exclusão do que no tratramento de controle, mas como esperado, não houve diferenças nas abundâncias de insetos alados terrestres entre os tratamentos; insetos terrestres foram três vezes mais abundantes que os insetos aquáticos emergentes. PERMANOVA revelou que a abundância de predadores terrestres foi afetada pelo tratamento de exclusão de subsídios, mas não a biomassa. No entanto, análises univariadas mostraram que apenas 11,5% dos taxons de predadores (Anyphaenidae, Araneidae e Theridiidae) diminuíram sua abundância no tratamento de exclusão e o 7,7% deles (Araneidae e Theridiidae) diminuíram sua biomassa na exclusão. A abundância dos fitófagos, detritívoros e onívoros não foi afetada pela exclusão de subsídios, mas a biomassa dos fitófagos ...
Keywords: Ecologia das florestas tropicais; Predação (Biologia); Inseto - Comportamento; Inseto aquatico; Inseto florestal; Ecossistemas; Florestas tropicais; Predation (Biology)